A new sliding mode approach to asymptotic feedback linearisation with application to the control of non-flat systems - Lu, Xiao-Yun; Spurgeon, Sarah K. (Zielona Góra: Uniwersytet Zielonogórski)
A dynamic sliding mode controller design method is proposed. The method uses a novel choice of the sliding surface to effect asymptotic linearisation of nonlinear differential input output systems and a class of state space systems. The stability of the overall system, i.e. a canonical state space form with a dynamic feedback, is analysed.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka